Socialised Shopper: An empirical study of shoppers’ browsing psychology, social media and share to purchase behavior - Singh, Samarth; Maitri (International Journal of Psychosocial Rehabilitation, 2020)
As Indian economy is moving towards digitalization there would be more digital  shopper- retailer interactions like  social media interactions etc. Recognizing the importance of social media during shoppers purchase journey and  their browsing psychology in a retail outlet , this paper reports results from an empirical study that investigates  shoppers browsing psychology and social media behaviour undertaken in organized retail in Delhi. It studies  shoppers social media behaviour on retailer’s social pages along with the share to purchase behaviour so as to  understand the usefulness of such interactions.Further it studies shoppers browsing psychology in terms od usage of  shopping list, on pack information and browsing of aisles. Five hundred shoppers’ data was attained using a survey  questionnaire. Study reveals that majority of the shoppers visit retailer’s social pages to avail exclusive discount  followed by  socializing with friends to know more about products they want to buy , to participate in competitions,  to earn rewards points, to provide product feedback , to avail after sales services and to launch complaints .  Further, highlighting the share to purchase behaviour it reveals that thirty eight percent ( five percent of total  shoppers ) of those who went to the retailer’s site through sharing on social media  have purchased the product  from physical store .Regarding browsing psychology only 19 percent shoppers frequently use shopping list,22  percent shoppers look for on pack information and go to intended isle directly and majority of shoppers go for  assistance to sales staff Research outcomes encourage retailers to implement technology driven targeted marketing.